Clindamycin 0.025% and Tretinoin 0.005% Cream for Infantile Acne Vulgaris - Gabriela Reginata; Sukmawati Tansil Tan; Listyani Gunawan (PT Kalbe Farma Tbk., 2019)
Acne vulgaris is an inflammatory disease of pilosebaceous unit marked by the presence of comedones, papules, pustules, nodules, and cysts. A boy aged 4 years old was reported of having red spots on his cheeks since the age of 1 month old. Erythematous papules and pustules with white heads were found in the facial area. Infantile acne diagnosis was considered. Combination of clindamycin 0.025% and tretinoin 0.005% cream was given to accelerate healing process and to prevent complications such as post-inflammatory hyperpigmentation. The patient’s condition was considerably better after 1 month. Acne vulgaris merupakan inflamasi kelenjar pilosebasea yang ditandai dengan komedon, papula, pustula, nodula, dan kista. Dilaporkan kasus anak laki-laki usia 4 tahun mempunyai bintik kemerahan di pipi sejak usia 1 bulan. Dijumpai papula dan pustula eritematous dengan white heads di wajah, didiagnosis sebagai infantile acne. Diberikan krim kombinasi clindamycin 0,025% and tretinoin 0,005% untuk terapi dan mencegah komplikasi hiperpigmentasi. Keadaan pasien lebih baik setelah terapi 1 bulan.